Perfil hematológico e atividade de colinesterases em jovens de regiões de fronteira agrícola do município de Belterra-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study aimed to analyze the hematological profile and cholinesterase activity in young individuals from border areas of the municipality of Belterra, assessing their exposure to pesticides. The research adopted a descriptive and cross-sectional approach, with data collected through and field research. A total of 50 students were analyzed based on information regarding residence, proximity to plantations, level of knowledge about pesticides, and blood samples for laboratory tests. The results showed that 60% (30/50) of participants live near agricultural areas, thus being potentially exposed to pesticides. Although 74% (37/50) of the young individuals were familiar with the concept of pesticides, only 38% were aware of their local use. Around 48% (24/50) of respondents reported symptoms after pesticide application, and 62% (31/50) do not treat water before consumption, increasing the risk of contamination. Laboratory analysis indicated no statistically significant differences in hematological and cholinesterase profiles between male and female individuals, with all values remaining within reference parameters. These findings reinforce the importance of awareness actions regarding pesticide risks, the implementation of preventive measures, and the continuous monitoring of hematological and cholinesterase biomarkers. Furthermore, the development of public policies to minimize the impacts of chronic exposure to these substances is essential to ensure the health and well-being of the local population.
Keywords: Perfil Hematológico; Colinesterases; Agrotóxicos; Exposição; Fronteira Agrícola; CNPQ:: CIÊNCIAS DA SAÚDE